Implementasi Kebijakan Pemanfaatan Sewa Barang Milik Negara: Tanah Pengairan Solo Valley Warken Kabupaten Lamongan (Studi di Desa Pelangwot Kecamatan Laren dan Desa Sedayulawas Kecamatan Brondong) - Sudrajat, Raharwindy Kharisma; Wanto, Alfi Haris; Supriyono, Bambang (Jurnal Ilmiah Administrasi Publik, 2021)
After the development of the floodway, the Solo Valley Warken Irrigation Land that has not been and is not used for irrigation needs can be used by the subject of the lease by paying a fee that has been determined by the Public Works Office for Water Resources (SDA) of Lamongan Regency so that it can be used to meet the needs of community land. which is increasing. As for the fees that are generated each year, it will be divided according to the cooperation agreement between the Public Company (PERUM) Jasa Tirta I and the Autonomous Regional Government of Lamongan Regency. Although the ratio of effectiveness between the target of receiving retribution and revenue realization is very effective, its contribution to PAD in Lamongan Regency is still far below the average.